REPRESENTASI SEJARAH INDONESIA DALAM NOVEL-NOVEL KARYA AYU UTAMI - Wiyatmi Wiyatmi Wiyatmi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe the form and representation of socio-political historical events in Ayu Utami’s novels. The data sources were four novels written by Ayu Utami, namely Saman, Larung, Manjali dan Cakrabirawa, and Cerita Cinta Enrico. They were analyzed using the New Historicism perspective. The findings are as follows. First, socio-political historical events in the novels are: (a) an event in Medan from 1 March to 16 April 1994, (b) 30 September Movement in 1965, (c) the tragedy of 27 July 1996 in Jakarta, (d)the rebellion by the Republic of Indonesia’s Revolutionary Government, 15 February 1958 in Padang,(e)the demonstration by students of Technology Institute of Bandung and the publication of the Student Struggle White Book in 1978. Second, the events are represented in parts integrated into the events that the characters experience. Historical events from factual events are contextualized in the novels. In the New Historicism perspective, socio-political historical events are presented to question historical truths previously recorded.